Pengaruh E-Servicescape Dalam Meningkatkan Loyalitas Pelanggan Melalui Kepercayaan Dan Perceived Value Sebagai Variabel Mediasi (Studi Pada Pengguna Shope Di Jawa Tengah) - Ramlah, Sri; Fatkhurrokhman, Tiyan; Barokah, Siti; Pratama, Wilson Chandra Teguh; Anggoro, Wisanggeni Bagus (Utiliti Project Solution, 2023)
This study examines the effect of e-servivescape on customer loyalty and to examine the mediating role of trust and perceived value in the relationship between e-servivescape to customer loyalty. This research conducted a survey of 110 Shopee marketplace users in Central Java. Research data were analyzed using Partial Least Square which was operated through the SmartPLS program. The results of the analysis show that e-servivescape has a positive and significant effect on customer loyalty, e-servivescape has a positive and significant effect on trust, e-servivescape has a positive and significant effect on perceived value, trust has a positive and significant effect on customer loyalty, perceived value has a positive and significant influence on customer loyalty. Mediation analysis reveals that trust and perceived value play a role in mediating the relationship between e-servivescape and customer loyalty.